Utilization of fermented chicken manure and catfish culture waste in recirculated sludge worm culture - Putri, Diana Sriwisuda; Supriyono, Eddy; Djokosetiyanto, Daniel (Indonesian Society of Scientific Aquaculture (ISSA), 2014)
ABSTRACT This study aimed to analyze the effect of utilization of chicken manure and catfish (Clarias sp.) waste on yield of sludge worm (Tubifex sp.) culture with recirculation systems in multi-storey container. The experimental design used was completely randomized design with four treatments and two replications. Treatments conducted were addition of fermented chicken manure into sediments (P0), fermented chicken manure into sediments and repetition once in five days (P1), fermented chicken manure into sediment and waste from intensive catfish farming (P2), fermented chicken manure into sediments and repetition once in five days and also waste from intensive catfish farming (P3). The container used to rear sludge worm was a wooden container at size of 100x50x15 cm3. Containers made multi-storey (three-level). The medium used was a sludge and chicken manure. Sludge worm was stocked as much as 100 g/m2. Silk worms were given additional fertilizer of fermented chicken manure about 500 g/container with repetition of administration done every five days. Parameters measured were individual abundance, biomass and water quality. The results showed that addition of fermented chicken manure into sediment and waste from intensive catfish farming was the best medium to increase the growth of silk worms with an average abundance at 1,697 ind/m2, and average biomass at 6,470.98 g/m2. Keywords: sludge worm, recirculation, storey container, fermentation chicken manure, catfish waste protein ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh pemanfaatan kotoran ayam dan limbah lele (Clarias sp.) terhadap hasil panen cacing sutra (Tubifex sp.) dengan sistem resirkulasi dalam wadah bertingkat. Rancangan percobaan yang digunakan adalah rancangan acak lengkap dengan empat perlakuan dan masing-masing terdiri atas dua ulangan. Perlakuan yang diterapkan adalah pemberian kotoran ayam fermentasi di sedimen (P0), pemberian kotoran ayam fermentasi di sedimen dan pengulangan lima hari sekali (P1), pemberian kotoran ayam fermentasi di sedimen dan pemberian limbah dari budidaya lele intensif (P2), pemberian kotoran ayam fermentasi di sedimen dan pengulangan lima hari sekali dan pemberian limbah dari budidaya lele intensif (P3). Wadah penelitian yang digunakan untuk budidaya cacing sutra adalah kotak kayu berukuran 100x50x15 cm3. Wadah dibuat bertingkat (tiga tingkat). Media yang digunakan yaitu lumpur dan kotoran ayam. Cacing sutra ditebar sebanyak 100 g/m2. Cacing sutra diberi pupuk tambahan berupa kotoran ayam fermentasi sebanyak 500 g/wadah dengan pengulangan lima hari sekali. Parameter yang diamati meliputi kelimpahan individu, biomassa dan kualitas air. Hasil penelitian menunjukkan bahwa pemberian kotoran ayam fermentasi di sedimen dan pemberian limbah dari budidaya lele intensif (P2) merupakan media pemeliharaan terbaik untuk meningkatkan pertumbuhan cacing sutra dengan kelimpahan rata-rata sebesar 1.697 ind/m2 dan rata-rata biomass sebesar 6.470,98 g/m2. Kata kunci: cacing sutra, resirkulasi, wadah bertingkat, kotoran ayam fermentasi, limbah ikan lele